2018
DOI: 10.1080/21664250.2018.1466676
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the hydrodynamic impact of tsunami-like waves against impervious free-standing buildings

Abstract: Tsunamis, landslide-generated waves, and dam failures are rare, but highly destructive phenomena, associated with extreme loading on infrastructure. Recent events showed that specific measures must be taken to guarantee safety of both people and the built environment. This experimental study investigates the forces and moments exerted on free-standing buildings that are induced by both surges and bores. The hydrodynamic impact was characterized by high splash, subsequently followed by a quasi-steady flow aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
47
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 27 publications
15
47
1
2
Order By: Relevance
“…The hydrodynamic impact of bores and surges against free-standing impervious buildings was investigated experimentally by Cross (1967), Ramsden (1996), Asakura et al (2000), Arnason et al (2009), Nouri et al (2010), Foster et al (2017) and (Wüthrich et al, 2018a) among others. In addition, Nouri et al (2010) and Shafiei et al (2016) focused on the effect of building orientation on the resulting horizontal force.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The hydrodynamic impact of bores and surges against free-standing impervious buildings was investigated experimentally by Cross (1967), Ramsden (1996), Asakura et al (2000), Arnason et al (2009), Nouri et al (2010), Foster et al (2017) and (Wüthrich et al, 2018a) among others. In addition, Nouri et al (2010) and Shafiei et al (2016) focused on the effect of building orientation on the resulting horizontal force.…”
Section: Previous Studiesmentioning
confidence: 99%
“…and natural (hills, etc.) emerging obstacles (Lukkunaprasit et al, 2009 andWüthrich et al, 2018). All these obstacles can then be seen as impervious obstacles mounted on the bottom and emerging from the free-surface that the supercritical inflow must skirt it on the sides.…”
Section: Introductionmentioning
confidence: 99%
“…Mignot and Riviere (2010) additionally revealed the presence of a horseshoe vortex in the near bed region at the foot of the obstacle where the flow regime is subcritical. Recently, Wüthrich et al (2018) observed the transient transition between the wall jet and detached jumps around obstacles within transient flows reproducing tsunami waves.…”
Section: Introductionmentioning
confidence: 99%
“…However, the anti-sliding stability of the Geomembrane and the cement = tan 1 . Generally speaking, the foundation medium under Geomembrane is clay cushion (Wüthrich et al, 2018). Assuming that its shear modulus is G and its thickness is D, the clay cushion can be used to estimate k s :…”
Section: Geomembrane Modelmentioning
confidence: 99%